Hematological and Serum Biochemical Changes and Their Prognostic Value in Horses Spontaneously Poisoned by Crotalaria spectabilis - Câmara, Antonio Carlos Lopes; de Sousa Argenta, Verônica Lourença; de Moraes, Daniella Dianese Alves; Fonseca, Eduardo Ferreira; Fino, Tayná Cardim Moraes; Paludo, Giane Regina; Soto-Blanco, Benito (Frontiers in Veterinary Science, 2022)
Determining the prognosis of poisoning by plants containing pyrrolizidine alkaloids is usually challenging. This study aimed to identify important prognostic parameters that can determine the severity of spontaneous poisoning by Crotalaria spectabilis in horses. Blood samples from 42 horses spontaneously poisoned by oats contaminated with C. spectabilis seeds were evaluated. Complete blood counts (CBC) and serum biochemical tests [urea, creatinine, total protein, albumin, total and direct bilirubin concentrations, aspartate aminotransferase (AST), γ-glutamyl transferase (GGT), and creatine kinase (CK) activities] were performed. Horses were followed up for 12 months to determine the long-term survival rate; after 12 months, they were divided into two groups: survivors (n = 30) and non-survivors (n = 12). Horses spontaneously poisoned with C. spectabilis had higher levels of urea, globulin, bilirubin (total, direct, and indirect), AST, GGT, and CK than the reference values. Non-survivor horses showed significantly higher (p < 0.05) values of hemoglobin, GGT, and direct bilirubin than the survivor horses. Horses with serum GGT activity higher than 95 U/l had 14.0 times the risk of death compared to animals showing activities equal to or lower than this value, whereas horses with serum direct bilirubin concentration higher than 0.6 mg/dl (10.26 μmol/L) had 5.78 times the risk of death compared to the others. In summary, serum GGT activity and direct bilirubin concentration may be useful prognostic indicators for assessing the severity of C. spectabilis-poisoned horses.